The persistent challenges and strategies for effective rehabilitation among obstetric fistula patients at Kitovu Mission Hospital, Uganda: a qualitative study - Atuhaire, Shallon; Odukogbe, Akin-Tunde A.; Mugisha, John F.; Ojengbede, Oladosu A. (International Journal Of Community Medicine And Public Health, 2020)
Background: Obstetric fistula poses a great physical, psychosocial and economic burden to girls and women in low and middle-income countries. About 53% of the obstetric fistula patients may live with untreated fistula for more than a year, thus patients require rehabilitation as they await repair and after repair. Little qualitative research exists on rehabilitation particularly on the challenges and effective strategies that inspired this study. Methods: A cross-sectional qualitative research approach used in-depth interviews and key informant interviews to collect data from 10 obstetric fistula patients who had been registered by the Urogynecology Department, Kitovu Hospital within two years before the time of data collection status and 12 key informants who include hospital staffs engaged in the management of fistula and patients’ partners who were involved in caregiving. Data were analyzed thematically using ATLAS.ti 7.5. Results: The major constraints encountered during rehabilitation were limited resources for practice, inadequate counseling especially among immediate relatives, and inadequate capital for self-sustainability and limited employment opportunities. Key informants also mentioned the issue of limited resources, budget constraints, inadequate supervision and follow up of patients. Only one patient who had not had fistula repair had knowledge of rehabilitation. To address the challenges, the participants suggested the need for rehabilitation despite repair status. They required more knowledge about sustainable livelihood programs and cash grants. Conclusions: The patients identified socioeconomic, institutional and political challenges to their rehabilitation. They emphasized the need for improved political commitment, adequate budget, and resource allocation and regular support supervision to ensure their effective rehabilitation.